Priority Factors of Online Food Purchasing By Young Muslims - Fitri Eka Aliyanti; Muhammad Iqbal; Rheyza Virgiawan (UIN Raden Mas Said Surakarta, 2020)
This research is purposed to determine the factors that influence online food purchase decision making, by classifying them into certain classifications, namely primary dish, snack, and beverage, and emphasizing on purchase made online by Universitas Islam Indonesia (UII) Yogyakarta students. Furthermore, this research analyzes how halal awareness influences their purchasing decisions. The primary data sources were obtained using semi-structured interviews. The method of data analysis was performed by ranking respondents' answers using the scoring method. The result of this research shows that the most influential factors in purchasing decision making are halal awareness, with a sequence of elements from the most prioritized to those not as follows: halal awareness, favorite/preferences, taste, price, health, curiosity, advertisement, lifestyle, packaging, then bandwagon effect, and themost important factor influencing food online purchase decisions is halal awareness. Thus, from this study, it can be concluded that the majority of UII students have considered the halal aspect when making online food purchases.